2023
DOI: 10.1002/cctc.202300522
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐efficient Electrochemical Hydrogen Production Combined with Biomass Oxidation Using Polyoxometalate and Metal Salts

Abstract: Biomass oxidation in anode electrolyte solution is investigated for energy‐efficient hydrogen production. The redox of polyoxometalate (POM) as both biomass oxidation catalyst in the solution and charge carrier through regeneration at the graphite electrode promotes hydrogenation generation at the cathode, but suffers from a limited rate of biomass degradation due to the complex structure of solid lignocellulosic biomass. Herein, transition metal salts (CuCl2, CrCl3 and FeCl3) are studied as the synergistic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The results indicated that the electro-oxidation reaction occurred at the anode over the graphite electrode due to the Fe +3 /Fe +2 redox couple and that the reduced Fe +2 was reoxidised to Fe +3 , releasing electrons and protons [44]. During the pre-treatment of FeCl3 and glucose solution, Fe +3 was reduced to Fe +2 and glucose was oxidised [53]. Furthermore, the FeCl3-glucose solution changed from dark brown to dark red, confirming the degradation or oxidation of glucose.…”
Section: Analysis Of the Electrochemical Properties Of Fecl 3 -Mediat...mentioning
confidence: 99%
“…The results indicated that the electro-oxidation reaction occurred at the anode over the graphite electrode due to the Fe +3 /Fe +2 redox couple and that the reduced Fe +2 was reoxidised to Fe +3 , releasing electrons and protons [44]. During the pre-treatment of FeCl3 and glucose solution, Fe +3 was reduced to Fe +2 and glucose was oxidised [53]. Furthermore, the FeCl3-glucose solution changed from dark brown to dark red, confirming the degradation or oxidation of glucose.…”
Section: Analysis Of the Electrochemical Properties Of Fecl 3 -Mediat...mentioning
confidence: 99%